Kemampuan representasi verbal siswa melalui menulis jurnal matematika - Syifa, Fatimatus; Sudirman, Sudirman; Purwanto, Purwanto (UNIVERSITAS NEGERI MALANG, 2022)
This study aims to analyze students' verbal representation skills through mathematical journal writing activities. So that researchers can find out students' verbal representation skills through writing math journals. The topic that must be written in math journals is fractional material. This research use desciptive qualitative approach. The subjects of this study were grade 5 elementary school students. Data was collected by giving writing assignments on journal writing sheets and interviews. The results showed that the students' verbal representation ability through journal writing on the fraction concept indicator was still not correct. The language used to organize the presentation of ideas is still not systematic and logical. Students do not yet have verbal representation skills in making appropriate fractional expressions/pictures.